Perspectives and economic challenges of wind energy generation in the Northeastern region of Brazil (Research, Society and Development, 2022)
The dialogue around the electricity and renewable energy sector has become essential in several sectors, considering that the effects of extreme exploitation of the environment are strongly visible in all aspects. Due to the topicality and relevance of this subject, this article aims to present and analyze the perspectives and economic challenges in wind power generation in the Northeastern region, from 2011 to 2020. This research was based on the most recent publications on wind energy, both nationally and locally, and after a thorough analysis of all selected material, the outlines of the research body were defined. The research is based on how wind power generation processes have evolved, which has become a highly discussed topic due to the world dilemmas currently faced, on how the consumption and production of wind power has evolved in the region, and on how the tariffs for energy contrast with the systematic vulnerabilities presented in the Northeast, and finally, the observation of how the complexity of the Brazilian electrical system greatly affects the production of wind energy.